A highly-effective ionic liquid flame retardant towards fire-safety waterborne polyurethane (WPU) with excellent comprehensive performance. (28th September 2020) - Zhao, Zhuo; Guo, De-Ming; Fu, Teng; Wang, Xiu-Li; Wang, Yu-Zhong
Abstract: The flame-retardant waterborne polyurethane (WPU) has attracted more and more attentions from academia and industry. However, the addition of conventional flame retardants into WPU will damage the emulsion stability and introduce the potential further risk to demulsification and preparation failure. In this work, a novel flame-retardant approach is proposed, demonstrating outstanding efficiency, excellent compatibility and minimized side effect. A water-soluble ionic liquid 1-methyl-3-((6-oxidodibenzo[c, e] (Akindoyo et al., 2016; Chattopadhyay and Raju, 2007) [1, 2]oxaphosphinin-6-yl)methyl)-1-H-imidazol-3-ium-4-methylbenzenesulfonate ([Dmim]Tos) is applied as the additive flame retardant for the WPU dispersions. The resulting WPUs (WPU/[Dmim]Toses) display excellent flame retardancy via a low loading content (max 6.0 wt%) and potential adhesion applicable to industries, while maintaining the major comprehensive performance, including storage stability, mechanical property, thermal stability, transparency, hydrophobicity, etc. Effort from this work, besides of overcoming the explicit drawback, also serves as reference of novel methodologies to solve the compatibility issue between additive agents and WPU. Graphical abstract: Image 1 Highlights: Developing an easy-fabricated flame-retardant approach for WPU. As reference of novel methodologies to solve the compatibility issue. Outstanding flame retardancy and good comprehensive performance.